Partial Substitution of Soybean Meal by Slow-Release Nitrogen (Zenitro™) Decreases Feed Cost in Lactating Dairy Cows - Yogi, Ravindra K (Indian Journal of Animal Nutrition, 2021)
An on-farm trial was conducted in a commercial dairy farm to evaluate the effect of inclusion of slow-release nitrogen (SRN) on the performance of milking cows and associated monetary benefits. Twenty early lactating Holstein Friesian cows were used in the trial in such a way that first 18 days served the control (T1) and the next 21 days were treatment (T2) phase in which 1% SRN (Zenitro™, Kemin Industries) partially substituted soybean meal (SBM) on an isonitrogenous basis in the concentrates. All the cows were fed a total mixed ration comprising of corn silage, wheat straw and concentrate for a duration of 39 days. Results revealed that milk yield between the 2 groups did not differ (20.0±0.89 vs. 20.3±1.03 kg/d; P>0.05). Similarly, milk composition estimated in terms of fat and solid not fat was also not altered. Nevertheless, there was a net economic gain of ` 14.5/cow/d on incorporating SRN. Therefore, this study demonstrated that SRN at 1% level in the concentrate could effectively substitute a part of SBM for lactation diets, whilst also improving economic sustainability in dairy farming.